2015
DOI: 10.1016/j.jceh.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in Hepatic Encephalopathy: Mechanistic Aspects

Abstract: Hepatic encephalopathy (HE) is a major neurological complication of severe liver disease that presents in acute and chronic forms. While elevated brain ammonia level is known to be a major etiological factor in this disorder, recent studies have shown a significant role of neuroinflammation in the pathogenesis of both acute and chronic HE. This review summarizes the involvement of ammonia in the activation of microglia, as well as the means by which ammonia triggers inflammatory responses in these cells. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 81 publications
(102 reference statements)
1
77
0
3
Order By: Relevance
“…In contrast to our results, RXR agonists have been shown to have anti-inflammatory effects (Gonzalez et al, 2009; Kang et al, 2000; Lefterov et al, 2015; Uchimura et al, 2001). One plausible explanation for the conflicting results may be due to hepatic neuropathy caused by liver dysfunction, in which astrocytosis and microglial activation are characteristic pathological changes (Butterworth, 2013; Jayakumar et al, 2015). Although we did not assess the effects of lower doses of bexarotene treatment to potentially reduce these deleterious effects in the current study, the clinical application of this drug in aged patients to treat aging-associated cognitive decline requires great caution.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results, RXR agonists have been shown to have anti-inflammatory effects (Gonzalez et al, 2009; Kang et al, 2000; Lefterov et al, 2015; Uchimura et al, 2001). One plausible explanation for the conflicting results may be due to hepatic neuropathy caused by liver dysfunction, in which astrocytosis and microglial activation are characteristic pathological changes (Butterworth, 2013; Jayakumar et al, 2015). Although we did not assess the effects of lower doses of bexarotene treatment to potentially reduce these deleterious effects in the current study, the clinical application of this drug in aged patients to treat aging-associated cognitive decline requires great caution.…”
Section: Discussionmentioning
confidence: 99%
“…Increased [Ca 2+ ] i also occurs in brain slices exposed to as little as 1-2 mM ammonia, and inhibition of GS results in a significantly larger [Ca 2+ ] increases [153], perhaps due to impaired ammonia detoxification. The reason for the delayed response at relative low ammonia concentrations is a gradually developing, marked nitrosative and oxidative damage after ammonia exposure [154][155][156][157] Fig. 5 Similarity between effects of ammonia (5 mM) on protein expression of both NKCC1 and phosphorylated NKCC1 (p-NKCC1) in cultured rat astrocytes (a1, a2) and the effect of thioacetamideinduced acute liver failure in rats in vivo, leading to hyperammonemia (b1, b2).…”
Section: Cyclic Gmp and Nitric Oxidementioning
confidence: 99%
“…It is therefore important that cultured cerebral endothelial cells treated with ammonia also react with oxidative/nitrosative stress [161] and that the transcription factor NF-κB is activated in cortical endothelial cells from thioacetamide-treated animals [162]. A multitude of inflammatory mediators are increased in hepatic encephalopathy and microglia is activated by ammonia [157]. In liver cirrhosis patients with and without hepatic encephalopathy expression levels are altered for more than 1000 genes related to oxidative stress, microglia activation, receptor signaling, inflammatory and anti-inflammatory pathways, cell proliferation, and apoptosis [163].…”
Section: Cyclic Gmp and Nitric Oxidementioning
confidence: 99%
“…However, other authors have shown increased levels of serum TNF‐α, IL‐1β, and IL‐6 and their arteriovenous differences consistent with a brain cytokine efflux in patients with a bout of HE. This supports the presence of a central nervous system inflammatory component (neuroinflammation) in HE …”
Section: Discussionmentioning
confidence: 99%